(untitled) (Terr@ Plural, 2021)
In general, trilobites had their moulting performed by the breakdown of the librigena, a region (more external) situated on the cephalon of those animals. However, phacopid (calmonid and homalonotid) trilobites from the Paraná Basin have shown a Salterian moulting pattern, differing from the other trilobites. This moult pattern consisted of the separation of all the cephalon to the thorax. So, this paper intends to demonstrate information regarding preservation standards resulting from behavior(moult) of trilobites from the Paraná Basin, as found in the literature specialized and studied scientific collections.